2022
DOI: 10.3389/fpls.2022.890949
|View full text |Cite
|
Sign up to set email alerts
|

Genes Encoding Potential Molecular Mimicry Proteins as the Specific Targets for Detecting Bursaphelenchus xylophilus in PCR and Loop-Mediated Isothermal Amplification Assays

Abstract: The introduction of the pine wood nematode (Bursaphelenchus xylophilus) to new areas has affected the international forestry industry because this pathogen causes pine wilt disease (PWD). Therefore, methods for the accurate and reliable detection of B. xylophilus are essential for controlling and managing this pest. The PCR and Loop-Mediated Isothermal Amplification (LAMP) techniques developed in this study involve species-specific primer sets targeting B. xylophilus genes encoding potential molecular mimicry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…These nematodes secrete proteins that contain a conserved 12-amino acid C-terminal motif, which is highly similar to plant CLAVATA3/ESR (CLE) ligand peptides 48 . Similarly, migratory endoparasitic nematodes like B. xylophilus have been found to produce thaumatin-like proteins and a cystain-like peptidase inhibitor 12 , 49 , which agreed with the present study. Recent studies have identified several proteins in plant-parasitic nematodes that could mimic host plant peptidase and peptidase inhibitors.…”
Section: Discussionsupporting
confidence: 92%
“…These nematodes secrete proteins that contain a conserved 12-amino acid C-terminal motif, which is highly similar to plant CLAVATA3/ESR (CLE) ligand peptides 48 . Similarly, migratory endoparasitic nematodes like B. xylophilus have been found to produce thaumatin-like proteins and a cystain-like peptidase inhibitor 12 , 49 , which agreed with the present study. Recent studies have identified several proteins in plant-parasitic nematodes that could mimic host plant peptidase and peptidase inhibitors.…”
Section: Discussionsupporting
confidence: 92%
“…LAMP ( Notomi et al., 2000 ) is a highly efficient nucleic acid amplification technology that can potentially improve disease diagnosis in plant protection. LAMP technology has been applied for detecting B. xylophilus and the methods have constantly been improved ( Kikuchi et al., 2009 ; Leal et al., 2015 ; Meng et al., 2022 ). LAMP assays can detect B. xylophilus with high sensitivity and efficiency; however, interpretation of LAMP reaction results has been a critical issue.…”
Section: Discussionmentioning
confidence: 99%
“…Isothermal amplification approaches, such as loop-mediated isothermal amplification (LAMP) and recombinant polymerase amplification (RPA), have been successfully applied to detect B. xylophilus . These approaches have eliminated the need for thermocycling instruments and can be used for real-time detection, thereby supporting field and point-of-care testing ( Zhou et al., 2022 ; Meng et al., 2022 ). However, these technologies generally are unable to distinguish nucleotide sequences that differ in only one, or even several, bases; they need to be optimized, and may result in false positives because of non-specific amplification, cross-contamination, and/or primer dimerization ( Wang et al., 2018 ; Joung et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%